Early glial activation precedes neurodegeneration in the cerebral cortex after SIV infection: A 3D, multivoxel proton magnetic resonance spectroscopy study. Issue 6 (17th February 2015) - Wu, WE; Babb, JS; Tal, A; Kirov, II; George, AE; Ratai, E‐M; Gonzalez, RG; Gonen, O
<x xml:space="preserve">Abstract</x> Objectives As ∼40% of HIV‐infected individuals experience neurocognitive decline, we investigated whether proton magnetic resonance spectroscopic imaging (1H‐MRSI) detects early metabolic abnormalities in the cerebral cortex of a simian immunodeficiency virus (SIV)‐infected rhesus monkey model of neuroAIDS. Methods The brains of five rhesus monkeys before and 4 or 6 weeks after SIV infection (with CD8+ T‐cell depletion) were assessed with T2‐weighted quantitative magnetic resonance imaging (MRI) and 16×16×4 multivoxel 1H‐MRSI (echo time/repetition time = 33/1440 ms). Grey matter and white matter masks were segmented from the animal MRIs and used to produce cortical masks co‐registered to 1H‐MRSI data to yield cortical metabolite concentrations of the glial markers myo‐inositol (mI), creatine (Cr) and choline (Cho), and of the neuronal marker N‐acetylaspartate (NAA). The cortex volume within the large, 28 cm3 (∼35% of total monkey brain) volume of interest was also calculated for each animal pre‐ and post‐infection. Mean metabolite concentrations and cortex volumes were compared pre‐ and post‐infection using paired sample t‐tests. Results The mean (± standard deviation) pre‐infection concentrations of the glial markers mI, Cr and Cho were 5.8 ± 0.9, 7.2 ± 0.4 and 0.9 ± 0.1 mM, respectively; these concentrations increased 28% (p ≈ 0.06), 15% and 10% (both p < 0.05), respectively, post‐infection. The mean concentration of neuronal marker NAA remained unchanged (7.0 ± 0.6 mM pre‐infection vs. 7.3 ± 0.8 mM post‐infection; p ≈ 0.37). The mean cortex volume was also unchanged (8.1 ± 1.1 cm3 pre‐infection vs. 8.3 ± 0.5 cm3 post‐infection; p ≈ 0.76). Conclusions These results support the hypothesis that early cortical glial activation occurs after SIV infection prior to the onset of neurodegeneration. This suggests HIV therapeutic interventions should potentially target early glial activation in the cerebral cortex.